High-strength heat-insulation aerogel structure with dual multi-scale design and preparation method thereof

The high-strength thermal insulation aerogel structure with dual multi-scale design solves the problems of insufficient stiffness and thermal stability of traditional spacecraft aerogel structures under extreme conditions, and achieves thermal protection effects of high strength, low thermal conductivity, thermal shock resistance and ablation resistance.

CN121157445APending Publication Date: 2025-12-19李姝临
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511390642.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Traditional aerogel structures on spacecraft surfaces lack structural rigidity, thermal protection, and thermal stability under extreme high temperatures and mechanical loads. Existing designs are prone to deformation and cracking at high temperatures and have insufficient resistance to ablation.

Method used

The high-strength thermal insulation aerogel structure, which adopts a dual multi-scale design, consists of an upper carbon-carbon composite material plate, a lower carbon-carbon composite material plate, and a titanium alloy honeycomb skeleton. Through multi-scale design and material combination, an integrated thermal protection structure of C/C shell-titanium alloy lattice-multi-scale aerogel is formed, which enhances structural stability and thermal protection performance.

Benefits of technology

It significantly improves the thermal protection performance and stability of the structure, increases in-plane compressive strength and flexural strength, reduces thickness thermal conductivity, resists high-temperature ablation, and can maintain integrity and thermal insulation performance in high-temperature and high-heat-flux environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121157445A_ABST
    Figure CN121157445A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength heat-insulation aerogel structure with a dual multi-scale design and a preparation method thereof, relates to the technical field of thermal protection of spacecrafts, and in particular relates to the high-strength heat-insulation aerogel structure with the dual multi-scale design and the preparation method thereof. The invention aims to solve the problems of insufficient structural rigidity and poorer thermal protection property and thermal stability of the traditional spacecraft surface aerogel structure under the conditions of extreme high temperature and mechanical load. The structure is composed of an upper carbon-carbon composite material plate, a lower carbon-carbon composite material plate, an alloy skeleton and a filler. The method comprises the following steps: 1, preparing a multi-scale C / C composite material; 2, designing and preparing a titanium alloy honeycomb framework; 3, proportioning the multi-scale aerogel; 4, in-mold in-situ gelation; 5, drying and heat treatment; and 6, assembling and solidifying. The porosity of the aerogel is 85-98%, the structure has high rigidity and thermal protection performance, and the aerogel is applied to the field of aerospace thermal protection.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of spacecraft thermal protection, and particularly relates to a high-strength thermal insulation aerogel structure with a dual multi-scale design and a preparation method thereof. BACKGROUND

[0002] In the current rapid development of the aerospace industry, humans have higher requirements for the flight speed, task radius and detection accuracy of spacecraft. The thermal protection problem of spacecraft during hypersonic flight and reentry into the atmosphere has become one of the core technical bottlenecks restricting the successful implementation of space missions. When a spacecraft flies at a hypersonic speed or reenters the earth's atmosphere from space, it will have intense friction and compression with the atmosphere, forming a high-temperature gas flow with a temperature of thousands of degrees Celsius on the surface, accompanied by extremely strong thermal shock, aerodynamic load and ablation erosion and other extreme environments. In this process, the spacecraft thermal protection system needs to simultaneously meet the requirements of high-efficiency thermal insulation, excellent mechanical stability and ablation resistance to ensure the normal operation of the equipment in the cabin and the safety of astronauts, and therefore, it is of great strategic significance to develop high-performance thermal protection materials and structure systems.

[0003] The traditional spacecraft thermal protection system generally adopts a composite structure of a metal substrate + a refractory coating, wherein the metal substrate mainly bears the mechanical support function, and the refractory coating relies on its high-temperature resistance to achieve preliminary thermal insulation. This structure can meet the relatively mild thermal environment requirements in early low-speed spacecraft missions, for example, in the thermal protection scenarios of low-orbit satellite reentry or subsonic aircraft, it can block the heat transfer to the cabin to a certain extent. However, with the breakthrough of aerospace technology in the fields of hypersonic weapons, deep space exploration return capsules, reusable spacecraft and the like, the severity of the thermal environment has increased exponentially - the surface heat flux density of the return capsule during reentry can reach 1000 kW / m 2 The above local temperature even breaks through 3000 DEG C, and at the same time, it needs to withstand hundreds of kilopascals of aerodynamic pressure and high-frequency vibration load. Under such extreme conditions, the limitations of the traditional thermal protection structure are increasingly prominent: the metal substrate is prone to softening and creep at high temperatures, resulting in a decrease in the overall stiffness of the structure; the refractory coating and the metal substrate have a large difference in the coefficient of thermal expansion, and are prone to interface peeling and cracking under repeated thermal shock, and in severe cases, the coating will fall off as a whole, losing the thermal protection function. In addition, the traditional structure has low thermal insulation efficiency, and in order to meet the design thermal insulation requirements, the structure thickness needs to be increased, which not only increases the takeoff weight of the spacecraft, but also affects the aerodynamic shape design of the spacecraft, further restricting the performance improvement of the spacecraft.

[0004] To solve the shortcomings of traditional thermal protection structure, researchers turn their eyes to aerogel materials with ultra-low thermal conductivity and high porosity. Aerogel, with its unique nano-porous structure, can effectively inhibit the three heat transfer modes of gas convection, solid conduction and thermal radiation, showing outstanding advantages in high-temperature thermal insulation field. It has been widely used in spacecraft thermal protection systems by international top aerospace agencies such as NASA. For example, the hypersonic thermal insulation airbag (HIAD) developed by NASA uses silicon-based aerogel as the core insulation layer. Through the high-efficiency thermal insulation performance of aerogel, the surface heat flux density during reentry of the spacecraft is reduced by more than 50%, greatly reducing the weight of the thermal protection system and providing key support for flexible reentry technology of large-size spacecraft. In addition, during the entry, descent and landing (EDL) process of Mars probe, aerogel is also used for local thermal protection of the probe cabin, successfully coping with the special thermal environment challenge of the thin atmosphere on Mars.

[0005] Although aerogel materials have significant advantages in thermal insulation performance, existing aerogel thermal protection structures still have technical bottlenecks that are difficult to break through. Currently, the aerogel structures used on the surface of spacecraft mostly adopt a composite form of "metal plate sandwich" or "honeycomb structure", that is, a metal plate or honeycomb core material is used to provide mechanical support, and aerogel is filled or attached inside the support structure. Although this structure design improves the compression resistance of aerogel to some extent, the problem of insufficient structural stability under the coupling of extreme high temperature and complex mechanical load is still prominent: on the one hand, the softening of the metal support structure at high temperature will directly lead to the decline of the overall bearing capacity of the aerogel structure, and when facing the fluctuation of aerodynamic pressure in hypersonic flight, the structure is prone to deformation and collapse; on the other hand, aerogel itself is relatively brittle and prone to micro-cracks under the action of vibration and impact load. These micro-cracks will continue to expand with the increase of thermal cycle times, eventually leading to the fragmentation of the aerogel structure and the loss of thermal insulation performance. At the same time, the existing aerogel structure has poor ablation resistance. Under the condition of high-temperature gas scouring or local high-temperature ablation, the nano-porous structure of aerogel is easily damaged, resulting in sintering and carbonization, which leads to a sharp increase in thermal conductivity and a significant decline in thermal protection performance.

[0006] In view of the core problems of the existing aerogel structure on the surface of spacecraft, such as insufficient structural stiffness, easy to decay of thermal protection performance, and poor thermal stability under extreme high temperature and mechanical load conditions, a new structure design concept and preparation method are urgently needed. SUMMARY

[0007] The present application is to solve the problems of insufficient structural stiffness, poor thermal protection and thermal stability of traditional aerogel structure on the surface of spacecraft under extreme high temperature and mechanical load conditions. A high-strength thermal insulation aerogel structure with dual multi-scale design and a preparation method thereof are provided.

[0008] A high-strength thermal insulation aerogel structure with a dual multi-scale design is composed of an upper carbon-carbon composite material plate, a lower carbon-carbon composite material plate, an alloy framework, and a filler; the material of the upper carbon-carbon composite material plate and the lower carbon-carbon composite material plate is carbon-carbon composite material, and the volume fraction of the reinforcing body in the carbon-carbon composite material is 40-75%; the alloy framework is a titanium alloy honeycomb lattice structure; the upper carbon-carbon composite material plate and the lower carbon-carbon composite material plate serve as skin structures, the alloy framework is clamped between the two to form a support frame, and the cell gap of the titanium alloy honeycomb lattice structure is filled with aerogel as a functional filler; and the filler is aerogel, and the porosity of the aerogel is 85-98%.

[0009] The preparation method of the above-mentioned high-strength thermal insulation aerogel structure with a dual multi-scale design is specifically performed according to the following steps:

[0010] I. Preparation of multi-scale carbon-carbon composite material: lay chopped carbon fibers on the main bearing layer to construct a hot face chopped layer on the hot face side; then form an isotropic or coarse lamellar structure pyrocarbon matrix on the hot face chopped layer and the main bearing layer by a low-temperature chemical vapor infiltration process to realize the construction of the material basic framework; functionalize the cold face side of the material basic framework to form a microporous scattering structure, complete the preparation of the multi-scale carbon-carbon composite material, and cut out the upper carbon-carbon composite material plate and the lower carbon-carbon composite material plate according to the design requirements;

[0011] II. Preparation of titanium alloy honeycomb framework: construct a titanium alloy honeycomb lattice structure according to the design requirements, realize the solid forming of the titanium alloy honeycomb framework by using a selective laser melting 3D printing technology, and perform annealing treatment after forming to obtain the titanium alloy honeycomb framework;

[0012] III. Preparation of multi-scale aerogel;

[0013] IV. Assembly and sol: position the titanium alloy honeycomb framework on the lower carbon-carbon composite material plate, and surround the edges with tearable adhesive tape or temporary sealing rings; then perform vacuum and back pressure circulation operations; inject the multi-scale aerogel in a partitioned manner under a vacuum state until the cells of the titanium alloy honeycomb framework are overflowed; allow the sol to gel to obtain a gel structure;

[0014] V. Drying and post-treatment: perform supercritical CO2 drying treatment on the gel structure, and then perform post-calcination and annealing treatment to obtain a structure to be assembled;

[0015] VI. Final assembly: fixedly connect the upper carbon-carbon composite material plate to the structure to be assembled by mechanical fitting, and then perform edge sealing and air hole treatment; perform slow temperature rising annealing treatment in an inert or air atmosphere to obtain a high-strength thermal insulation aerogel structure with a dual multi-scale design.

[0016] The beneficial effects of the present application are:

[0017] The application aims at the problem that the thermal insulation structure is easy to produce delamination, pulverization and "thermal bridge" short circuit due to thermal shock and mechanical coupling under reentry / hypersonic working conditions, and provides an integrated thermal protection structure and preparation process of C / C shell-titanium alloy lattice-multiscale aerogel. The C / C shell breaks and bends the thickness direction heat conduction path through the multiscale design in the thickness direction, so that the heat is scattered and the interface thermal resistance is affected multiple times in the conduction process, which significantly increases the equivalent thermal resistance and reduces the thickness thermal conductivity. At the same time, the structure increases the interface and defect density in the millimeter-micron-nanometer multiscale, suppresses the continuous high-conducting path and avoids the Z-direction thermal bridge, reduces the thickness thermal conductivity and improves the interlayer toughness while ensuring the in-plane stiffness; the titanium alloy lattice / honeycomb structure provides constraint and cooperative deformation, suppresses the aerogel compression and instability, and reduces the cracking tendency of the structure; at the same time, the multi-peak pore aerogel and the compounded radiation suppression particles and short fiber reinforcement weaken the solid and radiation heat transfer; in summary, the application realizes the synergistic improvement of low thermal conductivity, low deformation and high reliability under high temperature and high heat flow. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 It is a structural schematic diagram of a high-strength thermal insulation aerogel structure with double multiscale design, wherein 1 is an upper carbon-carbon composite plate, 2 is an alloy framework, 3 is a filler, and 4 is a lower carbon-carbon composite plate;

[0019] Figure 2 It is a structural schematic diagram of the alloy framework in the embodiment;

[0020] Figure 3 It is a multi-peak pore size distribution diagram of the aerogel in the embodiment;

[0021] Figure 4 It is a micro-morphology diagram of carbon fibers with different aspect ratios in the embodiment; wherein a~f are the raw material representations of short-cut carbon fibers with aspect ratios from large to small. DETAILED DESCRIPTION

[0022] Specific implementation manner one: the high-strength thermal insulation aerogel structure with double multiscale design in the embodiment is composed of an upper carbon-carbon composite plate, a lower carbon-carbon composite plate, an alloy framework and a filler; the materials of the upper carbon-carbon composite plate and the lower carbon-carbon composite plate are both carbon-carbon composite materials, and the volume fraction of the reinforcing body in the carbon-carbon composite material is 40~75%; the alloy framework is a titanium alloy honeycomb lattice structure; the upper carbon-carbon composite plate and the lower carbon-carbon composite plate serve as skin structures, the alloy framework is clamped between the two to form a support frame, and the cell gap of the titanium alloy honeycomb lattice structure is filled with aerogel as a functional filler; the filler is aerogel, and the porosity of the aerogel is 85~98%.

[0023] The reinforcing body in the embodiment refers to the total volume fraction of the amount of carbon fibers in the carbon / carbon composite material, including the short carbon fibers on the hot surface, the 3D woven carbon fibers in the load-bearing layer, and the micro-short carbon fibers on the cold surface.

[0024] The carbon / carbon composite material used in the embodiment replaces the combination of the metal plate and the refractory coating used in the outer shell of the traditional aerogel structure: the C / C composite material has excellent high-temperature performance, ablation resistance, and mechanical properties, can maintain structural stability and thermal stability in a high-temperature environment, the titanium alloy framework as a sandwich support structure has good mechanical properties and thermal stability, reducing the compression deformation of the aerogel can effectively improve the overall stiffness of the structure, and through the double multi-scale design of the carbon / carbon composite material and the filled aerogel, the thermal conductivity is further reduced. The new aerogel structure has excellent structural stability and thermal protection performance.

[0025] Specific implementation method two: the difference between the embodiment and the specific implementation method one is that the alloy framework is a Ti-6Al-4V hexagonal honeycomb structure, the cell edge length is 7-15 mm, and the metal rod diameter is 0.5-2 mm; the total thickness of the high-strength thermal insulation aerogel structure with double multi-scale design is 5-30 mm, and the alloy framework thickness is 3-15 mm. The others are the same as the specific implementation method one.

[0026] Specific implementation method three: the difference between the embodiment and the specific implementation method one is that the alloy framework is TC11 alloy. The others are the same as the specific implementation method one.

[0027] Specific implementation method four: the difference between the embodiment and the specific implementation method one is that the aerogel is SiO2 aerogel, Al2O3 aerogel, or carbon aerogel; the mass fraction of the radiation suppression particles in the aerogel is 2%-8%, the radiation suppression particles are a mixture of one or more of SiC, TiO2, ZrO2, and carbon black, and the median particle size is 100-500 nm; the mass fraction of the short fiber reinforcing body in the aerogel is 3%-15%, and the short fiber reinforcing body is quartz fiber or alumina fiber with a length of 3-8 mm. The others are the same as the specific implementation method one.

[0028] Specific implementation method five: the difference between the embodiment and the specific implementation method one is that the aerogel is Al2O3 aerogel with a porosity of 90-94%, and 3% of carbon black and 2% of SiC are added as radiation suppression phases, the mass fraction of the short fiber reinforcing body in the aerogel is 8%, and the short fiber reinforcing body is quartz fiber or alumina fiber with a length of 4-6 mm. The others are the same as the specific implementation method one.

[0029] Specific implementation method six: the preparation method of the high-strength thermal insulation aerogel structure with double multi-scale design in the embodiment is carried out according to the following steps:

[0030] I. Preparation of multi-scale carbon-carbon composite material: lay chopped carbon fibers on the main load-bearing layer to build the hot-face short-cut layer on the hot face side; then form an isotropic or coarse lamellar structure pyrolytic carbon matrix on the hot-face short-cut layer and the main load-bearing layer by low-temperature chemical vapor infiltration process to realize the construction of the material basic framework; functionalize the cold face side of the material basic framework to form a microporous scattering structure, complete the preparation of the multi-scale carbon-carbon composite material, and cut out the upper and lower carbon-carbon composite material plates according to the design requirements;

[0031] II. Preparation of titanium alloy honeycomb framework: build a titanium alloy honeycomb lattice structure according to the design requirements, realize the solid forming of the titanium alloy honeycomb framework by using selective laser melting 3D printing technology, and perform annealing treatment after forming to obtain the titanium alloy honeycomb framework;

[0032] III. Preparation of multi-scale aerogel;

[0033] IV. Assembly and sol: position the titanium alloy honeycomb framework on the lower carbon-carbon composite material plate, and surround the edges with tearable tape or temporary sealing ring; then perform vacuum and back pressure circulation operation; inject multi-scale aerogel into the partition under vacuum state until the cells of the titanium alloy honeycomb framework are overflowed; gel the sol by standing to obtain a gel structure;

[0034] V. Drying and post-treatment: perform supercritical CO2 drying treatment on the gel structure, and then perform post-calcination and annealing treatment to obtain a structure to be assembled;

[0035] VI. Final assembly: fix and connect the upper carbon-carbon composite material plate to the structure to be assembled by mechanical fitting, and then perform edge sealing and air hole treatment; perform slow temperature rising annealing treatment in inert or air atmosphere to obtain a high-strength thermal insulation aerogel structure with double multi-scale design.

[0036] The C / C composite material (carbon-carbon composite material) in this embodiment as a skin has a reinforcement volume fraction of 40-75%, and the main load-bearing layer adopts a 2.5D or 3D woven structure, which forms a three-dimensional load-bearing network of “in-plane tensile resistance-interlayer shear resistance” through the spatial interweaving of woven fibers, which can effectively resist the aerodynamic pressure and thermal shock load during spacecraft reentry and avoid skin cracking or falling off.

[0037] In this embodiment, the titanium alloy honeycomb lattice structure forms regular hexagonal or parallelogram support units; through “axial bearing of rod-shaped members + spatial dispersion of cells”, the local mechanical load is uniformly transmitted to the entire structure.

[0038] The annealing treatment in step two of the embodiment eliminates the residual stress in the 3D printing process, improves the yield strength of the titanium alloy framework, and effectively inhibits the instability of aerogel in the thermal expansion / compression process.

[0039] In the embodiment, the C / C skin is designed in multiple scales as "hot surface short-cut layer-pyrolytic carbon matrix-cold surface microporous scattering layer", which breaks the heat transfer path in the thickness direction from the heat transfer principle: the hot surface short-cut layer causes the first scattering of heat when entering the skin; the pyrolytic carbon matrix attenuates the heat for the second time through the interface thermal resistance; and the cold surface microporous scattering layer forms a large number of nanoscale micropores to cause the third scattering of the remaining heat.

[0040] In the embodiment, the annealing treatment in step two of the titanium alloy framework and the supercritical CO2 drying of the aerogel eliminate the residual stress and moisture in the material, avoiding the structural cracking caused by stress release or moisture evaporation at high temperature.

[0041] Specific embodiment seven: different from the specific embodiment six, the length of the short-cut carbon fiber in step one is 3-6 mm; the main bearing layer adopts a 2.5D or 3D woven carbon fiber structure, the volume fraction of the Z-direction yarn is 2-4%, and the spacing between the Z-direction yarns is 5-10 mm.

[0042] The low-temperature chemical vapor infiltration process in step one is specifically performed in the following steps: at 950-1050℃, using methane or propylene as the carbon source gas, argon or nitrogen as the carrier gas, and the gas flow ratio of carbon source gas: carrier gas = 1:(3-5); the reaction chamber pressure is controlled at 9-15 kPa, and the infiltration time is 50-100 h, until the density of the substrate reaches 1.2-1.5 g / cm 3 The pyrolytic carbon matrix forms an isotropic or coarse lamellar structure;

[0043] The functional treatment in step one is to configure an impregnation precursor containing micro-short carbon fibers and carbon black, and the solution is a thermosetting resin system, in which the mass fraction of the micro-short carbon fibers is 1-3%, the particle size is 100-300 μm, and the mass fraction of the carbon black is 0.5-1%; the prepared impregnation precursor is impregnated on the cold side of the material basic framework, and after the impregnation is completed, pyrolysis treatment is performed, and the impregnation-pyrolysis process is repeated 2-4 times until the overall density of the composite material reaches 1.6-1.8 g / cm 3 , the porosity is reduced to 5-10%, and a uniform microporous scattering structure is formed on the cold side of the material basic framework; the thermosetting resin is a phenolic resin or a polyimide resin;

[0044] The impregnation is to immerse the cold side of the material base skeleton into the impregnation precursor under the condition of vacuum degree ≤0.1 MPa, the impregnation pressure is 0.5-1.0 MPa, and the pressure is kept for 30-60 min; then the resin is crosslinked by curing at 150-200 ℃ for 2-4 h; then pyrolysis is carried out in an inert atmosphere to carbonize the resin to form a porous carbon matrix; the pyrolysis temperature program is: heating at 1-3 ℃ / min from room temperature to 600-800 ℃, and keeping the temperature at 600-800 ℃ for 2-4 h. The other parts are the same as embodiment six.

[0045] Embodiment eight: different from embodiment six, the process parameters of the first stage of the low-temperature chemical vapor infiltration process in step one are: the temperature is 980-1030 ℃, the pressure is 4-8 kPa, and the open porosity of the carbon-carbon composite material after the stage is controlled to be 18%-22%. The other parts are the same as embodiment six.

[0046] Embodiment nine: different from embodiment six, the impregnation-pyrolysis process is repeated for 3 times. The other parts are the same as embodiment six.

[0047] Embodiment ten: different from embodiment six, 10-30% volume fraction of pitch-based filaments are introduced into the main bearing layer in step one, and the filaments do not penetrate the thickness. The other parts are the same as embodiment six.

[0048] Embodiment eleven: different from embodiment six, the titanium alloy honeycomb lattice structure in step two is a regular hexagonal lattice structure, the unit regular hexagon has a side length of 7-15 mm and a height of 6-10 mm, and the metal rod has a diameter of 0.5-2 mm. The other parts are the same as embodiment six.

[0049] Embodiment twelve: different from embodiment six, the titanium alloy honeycomb lattice structure in step two is a parallelogram lattice structure. The other parts are the same as embodiment six.

[0050] Specific implementation method thirteen: the difference between this embodiment and specific implementation method six is that: in step three, the multi-scale aerogel is prepared by hydrolysis and polycondensation reaction through acid-base two-step catalytic process, using tetraethyl orthosilicate as silicon source, methyltrimethoxysilane or methyltriethoxysilane as co-precursor modifier, anhydrous ethanol as solvent, hydrochloric acid and ammonia as catalyst, to form a gel network, and the SiO2 wet gel is prepared; the SiO2 particle size is controlled to be 80-120 nm, the SiC radiation suppression particles with a particle size of 0.1-1 μm and the polyimide aerogel with a particle size of 1-10 μm are introduced; after the wet gel is aged under certain conditions, modification treatment is carried out, and then drying treatment is carried out, to obtain the multi-scale SiO2 aerogel. The others are the same as specific implementation method six.

[0051] In this embodiment, short fiber reinforcing bodies are added to the aerogel, and the short fibers form a randomly dispersed "microscopic support skeleton" inside the aerogel, which theoretically inhibits the brittle fracture of the aerogel, and the interface bonding force between the fibers and the aerogel matrix can disperse the crack propagation energy.

[0052] The aerogel adopts a multi-modal pore size design, and by introducing radiation suppression particles and polyimide aerogel particles, a "nanoscale pore-micron scale particle" microstructure is formed, which not only retains the low thermal conductivity characteristics of the aerogel, but also improves the microstructure stability through the space blocking effect of the particles, avoiding the "powdering" phenomenon at high temperatures.

[0053] Specific implementation method fourteen: the difference between this embodiment and specific implementation method six is that: in step four, the vacuum extraction and back pressure circulation is carried out at a pressure of-0.06~-0.09 MPa for 3-10 min, then 0.05-0.10 MPa back pressure is introduced, and the circulation is repeated for 2-3 times to remove the residual gas; the standing is carried out at room temperature-40℃ for 5-60 min. The others are the same as specific implementation method six.

[0054] In step four of this embodiment, the vacuum extraction at-0.06~-0.09 MPa and the back pressure circulation (2-3 times) at 0.05-0.10 MPa can completely remove the air in the titanium alloy honeycomb cells, and then the aerogel sol is injected in a partitioned manner under vacuum state, to ensure that the sol completely fills the cell gaps and avoid the formation of "thermal bridge" due to air bubbles remaining in the traditional glue injection process.

[0055] Specific implementation method fifteen: the difference between this embodiment and specific implementation method fourteen is that: in step four, the vacuum extraction and back pressure circulation is carried out at a pressure of-0.08 MPa for 3-10 min, then 0.08-0.10 MPa back pressure is introduced, and the circulation is repeated for 3 times to remove the residual gas; the standing is carried out at room temperature-40℃ for 5-60 min. The others are the same as specific implementation method fourteen.

[0056] Embodiment sixteen: different from embodiment fourteen, the standing is standing for 40-50 min at room temperature-40℃. The rest is the same as embodiment fourteen.

[0057] Embodiment seventeen: different from embodiment six, the drying process condition in step five: pressure 10-12 MPa, temperature 35-45℃, pressure maintaining 4-8 h, pressure releasing rate ≤0.5 MPa•min -1 , the linear shrinkage of the structure after drying is controlled to be ≤5%, the post-calcination is performed at a temperature of 200-400℃, and when applied to high-temperature scenarios, different annealing temperatures are selected according to the type of aerogel material, wherein when SiO2 aerogel or Al2O3 aerogel is used, the annealing temperature is 600-900℃, and when carbon aerogel is used, the annealing temperature is 800-1050℃ in an inert atmosphere. The rest is the same as embodiment six.

[0058] In this embodiment, drying is performed in the supercritical state of CO2, the solvent is separated in the form of gas, there is no capillary force, and the multi-modal pore structure of the aerogel can be completely preserved, thereby ensuring stable thermal insulation performance.

[0059] Embodiment eighteen: different from embodiment seventeen, the drying process condition in step five: pressure 11 MPa, temperature 40℃, pressure maintaining 6 h, pressure releasing rate ≤0.5 MPa•min -1 , the linear shrinkage of the structure after drying is controlled to be ≤5%, and the porosity is 89%-96%. The rest is the same as embodiment seventeen.

[0060] Embodiment nineteen: different from embodiment seventeen, the drying method in step five is atmospheric drying. The rest is the same as embodiment seventeen.

[0061] Embodiment twenty: different from embodiment six, in step six, a positioning pin / jig is used to ensure the thickness and parallelism of the structure, a dovetail / detent structure is used on the periphery of the structure, and the engagement gap is controlled to be 0.05-0.15 mm. The rest is the same as embodiment six.

[0062] In this embodiment, the skin and the titanium alloy framework are connected through “mechanical fitting + edge sealing”, the engagement gap is controlled to be 0.05-0.15 mm through the positioning pin / jig, a rigid overall structure is formed, the problem of interface separation of the traditional structure “skin-support” is solved, and the overall deformation resistance is improved.

[0063] Specific implementation manner twenty-one: the difference between this implementation manner and specific implementation manner six is that: the slow temperature rising annealing treatment in step six is treated at 150~250℃ for 2~6h, and the temperature difference between two sides of the large size component is controlled to be ≤10℃; finally, the residual deformation of the structure after assembly is ensured to be ≤0.3mm / 300mm. The others are the same as specific implementation manner six.

[0064] The residual stress is eliminated by slow temperature rising annealing in this implementation manner; the slow temperature rising annealing (2~6h) at 150~250℃ and the control of the temperature difference between two sides of the large size component to be ≤10℃ can make the thermal stress in the structure release slowly, and avoid cracking or deformation caused by temperature gradient.

[0065] The effect of the application is verified by the following test:

[0066] The preparation method of the high-strength heat-insulating aerogel structure with double multi-scale design is specifically carried out according to the following steps:

[0067] I. Preparation of multi-scale carbon-carbon composite material: lay chopped carbon fibers on the main bearing layer to construct the hot surface chopped layer on the hot surface side; then form an isotropic or coarse lamellar structure pyrolytic carbon matrix on the hot surface chopped layer and the main bearing layer by a low-temperature chemical vapor infiltration process to realize the construction of the material basic skeleton; functionalize the cold surface side of the material basic skeleton to form a microporous scattering structure, complete the preparation of the multi-scale carbon-carbon composite material, and cut out the upper carbon-carbon composite material plate and the lower carbon-carbon composite material plate according to the design requirements; the length of the chopped carbon fibers is 3~6mm; the main bearing layer adopts a 2.5D or 3D woven carbon fiber structure, and the volume fraction of the Z-direction yarn is 2~4%, and the spacing between the Z-direction yarns is 5~10mm;

[0068] The low-temperature chemical vapor infiltration process is specifically carried out according to the following steps: at 950~1050℃, use methane or propylene as the carbon source gas, the carrier gas is argon or nitrogen, the gas flow ratio is carbon source gas: carrier gas = 1: (3~5), the reaction chamber pressure is controlled at 9~15kPa, and the infiltration time is 50~100h until the matrix density reaches 1.2~1.5g / cm 3 to form an isotropic or coarse lamellar structure pyrolytic carbon matrix;

[0069] The functionalization treatment is to configure an impregnation precursor containing micro-short carbon fibers and carbon black, and the solution is a thermosetting resin system, wherein the mass fraction of the micro-short carbon fibers is 1~3%, the particle size is 100~300μm, and the mass fraction of the carbon black is 0.5~1%; the prepared impregnation precursor is impregnated on the cold surface side of the material basic skeleton, and after the impregnation is completed, pyrolysis treatment is carried out, and the impregnation-pyrolysis process is repeated for 3 times until the overall density of the composite material reaches 1.6~1.8g / cm 3, the porosity is reduced to 5~10%, and a uniform microporous scattering structure is formed on the cold side of the material base skeleton; the thermosetting resin is a phenolic resin or a polyimide resin;

[0070] The impregnation is performed by immersing the cold side of the material base skeleton into the impregnation precursor under a vacuum degree of ≤0.1 MPa, and the impregnation pressure is 0.5~1.0 MPa, and the pressure is maintained for 30~60 min; then the resin is crosslinked by curing at 150~200℃ for 2~4 h; then pyrolysis is performed in an inert atmosphere to carbonize the resin to form a porous carbon matrix; the pyrolysis temperature program is: heating at 1~3℃ / min from room temperature to 600~800℃, and maintaining at 600~800℃ for 2~4 h;

[0071] II. Preparation of titanium alloy honeycomb skeleton: according to the design requirements, a titanium alloy honeycomb lattice structure is constructed, and selective laser melting 3D printing technology is used to realize the solid forming of the titanium alloy honeycomb skeleton, and after forming, annealing treatment is performed to obtain the titanium alloy honeycomb skeleton; the titanium alloy honeycomb lattice structure is a regular hexagonal lattice structure, the unit regular hexagon has a side length of 7~15 mm, a height of 6~10 mm, and a metal rod diameter of 0.5~2 mm; the SLM parameters are: layer thickness 30~60 μm, laser power 150~300 W, scanning speed 800~1200 mm•s -1 ; and stress relief treatment is performed;

[0072] III. Preparation of multi-scale aerogel; the multi-scale aerogel is prepared by using tetraethyl orthosilicate as a silicon source, methyltrimethoxysilane or methyltriethoxysilane as a co-precursor modifier, anhydrous ethanol as a solvent, hydrochloric acid and ammonia as catalysts, forming a gel network through hydrolysis and polycondensation reaction, and obtaining SiO2 wet gel; the SiO2 particle size is controlled to be 80~120 nm, SiC radiation suppression particles with a particle size of 0.1~1 μm and polyimide aerogel with a particle size of 1~10 μm are introduced; after aging the wet gel under certain conditions, modification treatment is performed, and then drying treatment is performed to obtain multi-scale SiO2 aerogel;

[0073] IV. Assembly and sol: the titanium alloy honeycomb skeleton is positioned on the lower carbon-carbon composite material plate, and a tearable adhesive tape or a temporary sealing ring is used to surround the edge; then vacuum and back pressure circulation operation is performed; multi-scale aerogel is injected in a partitioned manner under vacuum until the cells of the titanium alloy honeycomb skeleton are overflowed; the sol is gelled by standing to obtain a gel structure; the vacuum and back pressure circulation is performed by vacuumizing for 3~10 min under a pressure of -0.08 MPa, and then introducing a back pressure of 0.08~0.10 MPa, and repeating the cycle for 3 times to remove the residual gas; the standing is performed at room temperature~40℃ for 40~50 min;

[0074] V. Drying and post-processing: supercritical CO2 drying treatment is performed on the gel structure, followed by post-calcination and annealing treatment to obtain a structure to be assembled; the drying process conditions are: pressure 11 MPa, temperature 40℃, pressure holding time 6h, pressure relief rate ≤0.5MPa•min -1 ; the linear shrinkage of the structure after drying is controlled to be ≤5%, and the porosity is 89%~96%; the post-calcination is performed at a temperature of 200~400℃; when applied to a high-temperature scene, the annealing temperature is 600~900℃;

[0075] VI. Final assembly: the carbon-carbon composite plate is fixedly connected to the structure to be assembled by mechanical fitting, followed by edge sealing and air hole treatment; slow temperature rising annealing treatment is performed in an inert or air atmosphere to obtain a high-strength thermal insulation aerogel structure with a double multi-scale design; positioning pins / jigs are used to ensure the thickness and parallelism of the structure, and dovetail / detent structures are used to cooperate around the structure, with a clamping gap of 0.05~0.15mm; the slow temperature rising annealing treatment is performed at a temperature of 150~250℃ for 2~6h, and the temperature difference between the two sides of the large-size component is controlled to be ≤10℃; finally, the residual deformation of the assembled structure is ensured to be ≤0.3mm / 300mm.

[0076] A high-strength thermal insulation aerogel structure with a double multi-scale design obtained from Example One achieves a breakthrough in performance. Experimental data show that this structure not only has excellent structural mechanical properties, with in-plane compressive strength and bending strength reaching 445MPa and 378MPa respectively, far exceeding traditional thermal insulation materials, but also exhibits excellent thermal insulation and reliability in extreme thermal environments. In a high-temperature hot surface environment, the material's in-plane thermal conductivity is as low as 0.0729W / (m·K), which can produce a super significant thermal insulation temperature difference. At the same time, after rigorous thermal shock cycling and high-temperature ablation tests, the material structure is intact without cracking, and the linear ablation rate is as low as 0.05mm / s, which comprehensively demonstrates the significant advantages of high strength, low thermal conductivity, thermal shock resistance and ablation resistance, and fully overcomes the technical bottlenecks of traditional thermal protection systems in high-temperature and high-heat flux environments.

Claims

1. A high-strength thermally insulating aerogel structure with a dual multi-scale design, characterized in that... The high-strength thermal insulation aerogel structure with a dual multi-scale design consists of an upper carbon-carbon composite material plate, a lower carbon-carbon composite material plate, an alloy skeleton, and fillers. Both the upper and lower carbon-carbon composite material plates are made of carbon-carbon composite materials, with the volume fraction of the reinforcement in the carbon-carbon composite material being 40-75%. The alloy skeleton is a titanium alloy honeycomb lattice structure. The upper and lower carbon-carbon composite material plates serve as a skin structure, with the alloy skeleton sandwiched between them to form a supporting frame. The cell voids of the titanium alloy honeycomb lattice structure are filled with aerogel as a functional filler. The filler is aerogel with a porosity of 85-98%.

2. The high-strength thermal insulation aerogel structure with a dual multi-scale design according to claim 1, characterized in that... The alloy skeleton is a Ti-6Al-4V hexagonal honeycomb structure with a cell side length of 7~15mm and a metal rod diameter of 0.5~2mm.

3. The high-strength thermal insulation aerogel structure with a dual multi-scale design according to claim 1, characterized in that... The aerogel is SiO2 aerogel, Al2O3 aerogel, or carbon aerogel; the mass fraction of radiation-suppressing particles in the aerogel is 2% to 8%, and the radiation-suppressing particles are one or a mixture of SiC, TiO2, ZrO2, and carbon black, with a particle center diameter of 100 to 500 nm; the mass fraction of short fiber reinforcement in the aerogel is 3% to 15%, and the short fiber reinforcement is quartz fiber or alumina fiber with a length of 3 to 8 mm.

4. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design as described in claim 1, characterized in that... The preparation method of the high-strength thermal insulation aerogel structure with dual multi-scale design is carried out according to the following steps: I. Preparation of multi-scale carbon-carbon composite materials: Short-cut carbon fibers are laid on the main support layer to construct a hot-side short-cut layer on the hot side; then, an isotropic or coarse-layered pyrolytic carbon matrix is ​​formed on the hot-side short-cut layer and the main support layer through a low-temperature chemical vapor infiltration process to realize the construction of the material's basic framework; the cold side of the material's basic framework is functionalized to form a microporous scattering structure, thus completing the preparation of the multi-scale carbon-carbon composite material; and the upper and lower carbon-carbon composite material plates are cut out according to the design requirements. II. Preparation of titanium alloy honeycomb skeleton: Construct a titanium alloy honeycomb lattice structure according to the design requirements, and use selective laser melting 3D printing technology to realize the solid forming of the titanium alloy honeycomb skeleton. After forming, it is annealed to obtain the titanium alloy honeycomb skeleton. III. Preparation of multi-scale aerogels; IV. Assembly and Sol-gel: Position the titanium alloy honeycomb skeleton on the lower carbon-carbon composite material plate and surround it with tearable tape or temporary sealing rings; then perform vacuuming and back pressure cycling operations; inject multi-scale aerogel in sections under vacuum until it fills the cells of the titanium alloy honeycomb skeleton; let it stand to allow the sol to gel, and obtain the gel structure. V. Drying and Post-treatment: The gel structure is dried with supercritical CO2, followed by post-calcination and annealing to obtain the structural parts to be assembled. VI. Final Assembly: The carbon-carbon composite material plate is fixedly connected to the structural component to be assembled by mechanical fitting, followed by edge sealing and venting treatment; and then slow-heating annealing is carried out in an inert or air atmosphere to obtain a high-strength thermal insulation aerogel structure with dual multi-scale design.

5. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... The chopped carbon fiber in step one has a length of 3-6 mm; the main bearing layer adopts a 2.5D or 3D woven carbon fiber structure, with a Z-axis yarn volume fraction of 2-4% and a Z-axis yarn spacing of 5-10 mm; The low-temperature chemical vapor infiltration process described in step one is carried out as follows: Methane or propylene is used as the carbon source gas at 950~1050℃, and argon or nitrogen is used as the carrier gas. The gas flow ratio is carbon source gas:carrier gas = 1:(3~5); the reaction chamber pressure is controlled at 9~15 kPa, and the infiltration time is 50~100 h, until the matrix density reaches 1.2~1.5 g / cm³. 3 Forming a pyrolytic carbon matrix with an isotropic or coarse lamellar structure; The functionalization process described in step one involves preparing an impregnation precursor containing micro-short carbon fibers and carbon black. The solution is a thermosetting resin system, wherein the mass fraction of micro-short carbon fibers is 1-3% with a particle size of 100-300 μm, and the mass fraction of carbon black is 0.5-1%. The prepared impregnation precursor is then used to impregnate the cold side of the material's basic skeleton. After impregnation, a pyrolysis treatment is performed, and this impregnation-pyrolysis process is repeated 2-4 times until the overall density of the composite material reaches 1.6-1.8 g / cm³. 3 The porosity is reduced to 5-10%, forming a uniform microporous scattering structure on the cold side of the material's basic framework; the thermosetting resin is phenolic resin or polyimide resin. The impregnation process involves immersing the cold side of the material's basic framework into the impregnation precursor under a vacuum of ≤0.1MPa, with an impregnation pressure of 0.5~1.0MPa, and maintaining this pressure for 30~60 minutes; followed by curing at 150~200℃ for 2~4 hours to allow the resin to crosslink. Then, pyrolysis is carried out in an inert atmosphere to carbonize the resin and form a porous carbon matrix. The pyrolysis temperature program is as follows: the temperature is increased from room temperature to 600-800℃ at a rate of 1-3℃ / min, and then held at 600-800℃ for 2-4 hours.

6. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... The titanium alloy honeycomb lattice structure described in step two is a regular hexagonal lattice structure, with the side length of the unit regular hexagon being 7~15mm, the height being 6~10mm, and the diameter of the metal rod being 0.5~2mm.

7. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... The process parameters for selective laser melting 3D printing described in step two are: layer thickness 30~60μm, laser power 150~300W, and scanning speed 800~1200mm•s. -1 .

8. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... In step three, the multi-scale aerogel is prepared by using tetraethyl orthosilicate as the silicon source, methyltrimethoxysilane or methyltriethoxysilane as the co-precursor modifier, anhydrous ethanol as the solvent, and hydrochloric acid and ammonia as catalysts. Through a two-step acid-base catalytic process, a gel network is formed by hydrolysis and polycondensation to obtain a SiO2 wet gel. The SiO2 particle size is controlled to be 80~120nm, and SiC radiation suppression particles with a particle size of 0.1~1μm and polyimide aerogel with a particle size of 1~10μm are introduced. After aging the wet gel under certain conditions, it is modified and then dried to obtain the multi-scale SiO2 aerogel.

9. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... The vacuuming and back pressure cycle in step four involves evacuating at a pressure of -0.06 to -0.09 MPa for 3 to 10 minutes, then introducing a back pressure of 0.05 to 0.10 MPa, and cycling 2 to 3 times to remove trapped gas; the settling is carried out at a temperature of room temperature to 40°C for 5 to 60 minutes.

10. The method for preparing a high-strength thermally insulating aerogel structure with a dual multi-scale design according to claim 4, characterized in that... The drying process conditions described in step five are: pressure 10~12MPa, temperature 35~45℃, pressure holding time 4~8h, and pressure release rate ≤0.5MPa•min. -1 The linear shrinkage of the structure after drying is controlled to be ≤5%; the post-calcination is carried out at a temperature of 200~400℃; when applied to high-temperature scenarios, different annealing temperatures are selected according to the type of aerogel material. When using SiO2 aerogel or Al2O3 aerogel, the annealing temperature is 600~900℃, and when using carbon aerogel, the annealing temperature is 800~1050℃ under an inert atmosphere.

Citation Information

Cited By

  • Design method of heat shield for aviation aircraft wheel

    CN121936052A

  • A design method of heat shield for aircraft wheel

    CN121936052B